Social and Historical Investigation of China’s Ethnic Minorities: Based on Political Stability and National Unity - Bao Longyuan; Dr. Mei Jun (Journal of Political Studies, 2023)
The social and historical investigation of China’s ethnic minorities was a major national political action in 50s-60s of the 20th Century, and it was of particular significance to the governance of the frontier, the maintenance of ethnic equality, and the long-term stability of China. In the era of underdeveloped information technology, the Communist Party of China (CPC) entered ethnic minorities areas, on the one hand, to understand the living conditions of ethnic minorities, and to facilitate the introduction of relevant supporting policies. On the other hand, the investigation process also publicized the CPC’s thought on governing the country, so that the people can more understand and trust the CPC, so as to promote national unity and political stability. Although this investigation has become a history, its significance, value and effect are still prominent for China’s political stability and national development today.Therefore, it is still of important practical significance to study the social and historical investigation of China’s ethnic minorities.